PENGARUH MEDIA AR MERGE CUBE TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN DAUR AIR - Siti Rahmawati, Mely; Enjang Yusup Ali; Ali Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT The low critical thinking skills of elementary school students are a challenge for 21st century learning, especially in abstract science materials such as water cycling. The use of Augmented Reality (AR) technology in elementary schools is still limited, especially the use of Merge Cubes which allows interactive three-dimensional visualization. This study aims to test the influence of AR Merge Cube media on students' critical thinking skills in water cycle learning. The study used a quasi-experimental method with a nonequivalent control group design. The sample consisted of 42 students in class V (22 experiments, 20 controls) who were selected purposively. The experimental class uses Merge Cube media, while the control class uses conventional media. The instrument is in the form of a multiple-choice test and a validated description. Data were analyzed using the Shapiro-Wilk normality test, Levene homogeneity test, independent t-test, N-Gain, and Cohen's effect size d. Results showed that the average posttest of the experimental class (80.68) was significantly higher than that of the control class (69.75) with a sig. of 0.001 < 0.05. The increase in N-Gain in the experimental class (73.76%) was higher than that of the control class (58.03%) with a large effect size (d=1.06). AR Merge Cube media has proven to be effective in improving students' critical thinking skills and can be an innovative alternative in science learning in elementary schools. ABSTRAK Rendahnya keterampilan berpikir kritis siswa sekolah dasar menjadi tantangan pembelajaran abad ke-21, terutama pada materi sains yang bersifat abstrak seperti daur air. Pemanfaatan teknologi Augmented Reality (AR) di sekolah dasar masih terbatas, khususnya penggunaan Merge Cube yang memungkinkan visualisasi tiga dimensi interaktif. Penelitian ini bertujuan menguji pengaruh media AR Merge Cube terhadap keterampilan berpikir kritis siswa pada pembelajaran daur air. Penelitian menggunakan metode quasi-experimental dengan nonequivalent control group design. Sampel terdiri dari 42 siswa kelas V (22 eksperimen, 20 kontrol) yang dipilih secara purposive. Kelas eksperimen menggunakan media Merge Cube, sedangkan kelas kontrol menggunakan media konvensional. Instrumen berupa tes pilihan ganda dan uraian yang telah divalidasi. Data dianalisis menggunakan uji normalitas Shapiro-Wilk, uji homogenitas Levene, independent t-test, N-Gain, dan effect size Cohen's d. Hasil menunjukkan rata-rata posttest kelas eksperimen (80,68) lebih tinggi signifikan daripada kelas kontrol (69,75) dengan sig. 0,001 < 0,05. Peningkatan N-Gain kelas eksperimen (73,76%) lebih tinggi dari kelas kontrol (58,03%) dengan effect size besar (d=1,06). Media AR Merge Cube terbukti efektif meningkatkan keterampilan berpikir kritis siswa dan dapat menjadi alternatif inovatif dalam pembelajaran sains di sekolah dasar.